Development of three-dimensional printed cultural fashion products using symbols of longevity. Issue 21 (November 2022) - Lee, Sung Kyu; Koo, Sumin
The COVID-19 pandemic has impacted the tourism industry, which makes it necessary to consider a variety of ways to overcome these challenges. The continuous effort to develop unique cultural fashion products and their original designs is necessary. This study aimed to develop cultural fashion products that people want to wear and purchase to revive the traditional symbols of longevity, called "shipjangsaeng, " with three-dimensional (3D) printing technology. Modernizing the symbols and the 3D printing technology can create new values of the convergence of tradition and technologies while providing customized benefits without inventory concerns. To achieve this, firstly, the preferred traditional symbols were extracted through a preference survey. Secondly, designs were virtually three-dimensionally simulated and surveyed to investigate the preferred designs. Thirdly, the selected designs were three-dimensionally modeled and printed, their flexural strength was tested, and they were fabricated into wearable products. The major results were as follows: (a) the most preferred patterns of longevity symbols were the sun and water/a wave; (b) the preferred item types were dresses and T-shirts using new technology such as 3D printing in achromic colors; (c) eight designs were proposed and the most preferred designs were designs 4 (a mini dress with water/wave patterns), 6 (a dress with a sun pattern), 7 (a T-shirt with a sun pattern), and 8 (a dress with a sun pattern); and (d) the four designs were fabricated into wearable cultural fashion products. The results of this study can provide insights to fashion designers and product developers when developing cultural fashion products by modernizing and reviving traditional symbols, enabling new values.